The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1124/dmd.114.062620
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Standing Mystery Solved: The Formation of 3-Hydroxydesloratadine Is Catalyzed by CYP2C8 But Prior Glucuronidation of Desloratadine by UDP-Glucuronosyltransferase 2B10 Is an Obligatory Requirement

Abstract: Desloratadine (Clarinex), the major active metabolite of loratadine (Claritin), is a nonsedating long-lasting antihistamine that is widely used for the treatment of allergic rhinitis and chronic idiopathic urticaria. For over 20 years, it has remained a mystery as to which enzymes are responsible for the formation of 3-hydroxydesloratadine, the major active human metabolite, largely due to the inability of any in vitro system tested thus far to generate this metabolite. In this study, we demonstrated that cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
(59 reference statements)
2
42
0
Order By: Relevance
“…The N-glucuronide of desloratadine is highly unstable (both before and after 3-hydroxylation by CYP2C8). We were unable to detect desloratadine N-glucuronide or 3-hydroxydesloratadine N-glucuronide by LC-MS/MS in our previous study (Kazmi et al, 2015). Instability is a characteristic property of certain N-glucuronides (Ciotti et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The N-glucuronide of desloratadine is highly unstable (both before and after 3-hydroxylation by CYP2C8). We were unable to detect desloratadine N-glucuronide or 3-hydroxydesloratadine N-glucuronide by LC-MS/MS in our previous study (Kazmi et al, 2015). Instability is a characteristic property of certain N-glucuronides (Ciotti et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Metabolic scheme for the conversion of desloratadine to 3-hydroxydesloratadine. Desloratadine is converted to an unstable N-glucuronide by UGT2B10 followed by CYP2C8-dependent hydroxylation to 3-hydroxydesloratadine as described previously (Kazmi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially considered an orphan enzyme, more recent studies have shown that UGT2B10, like UGT1A4, catalyzes the N-glucuronidation of a number of xenobiotics that incorporate an aliphatic tertiary amine or aromatic N-heterocyclic group (Kaivosaari et al, 2011). Known substrates are nicotine and its oxidation product cotinine (Chen et al, 2007;Kaivosaari et al, 2007); desloratadine (Kazmi et al, 2015a); medetomidine (Kaivosaari et al, 2008); the tricyclic antidepressants (TCAs) amitriptyline, clomipramine, imipramine, and trimipramine (Chen et al, 2007;Zhou et al, 2010;Kato et al, 2013); several tobacco-specific nitrosamines (Chen et al, 2008); RO5263397 (Fowler et al, 2015); and miscellaneous drugs that include diphenhydramine, ketoconazole, ketotifen, midazolam, olanzapine, pizotifen, and tamoxifen (Erickson-Ridout et al, 2011;Kato et al, 2013). Consistent with the known selectivity of UGT1A4 for N-glucuronidation (Kubota et al, 2007), most, if not all, UGT2B10 substrates are additionally glucuronidated by UGT1A4 and biphasic kinetics are frequently observed when human liver microsomes (HLM) are used as the enzyme source (Kaivosaari et al, 2011;Kato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%